Observations of upper tropospheric acetylene on Saturn: No apparent correlation with 2000 km-sized thunderstorms - Hurley, J; Irwin, P; Fletcher, L; Moses, J; Hesman, B; Sinclair, J; Merlet, C (2012)
Thunderstorm activity has been observed on Saturn via radio emissions from lightning discharges and optical detections of the lightning flashes on the planets nightside. Thunderstorms provide extreme environments in which specific atmospheric chemistry can be induced - namely through energy release via lightning discharges, and fast vertical transport resulting in rapid advection of tropospheric species. It is thus theorised that certain atmospheric trace species such as C 2H 2, HCN, and CO can be generated in the troposphere by large bursts of energy in the form of lightning, and transported upward towards the upper troposphere by the extreme dynamics of thunderstorms, where they should be observable by satellite instruments. In this work, high-spectral-resolution Cassini/CIRS observations from October 2005 through April 2009 are used to study whether there is an observable increase in upper tropospheric acetylene in regions of known normal thunderstorm activity. Using both individual measurements in which there is known thunderstorm activity, as well as large coadditions of data to study latitudinal-dependencies over the full disc, no systematic enhancement in upper tropospheric (100 mbar) C 2H 2 was detected around regions in which there are known occurrences of normally sized (2000 km) thunderstorms, or in normally sized thunderstorm-prone regions such as 40°S. It is likely that the magnitude of the enhancement theorised is too generous or that enhancements are not advected into the upper troposphere as vertical mixing rates in models would suggest, since Cassini/CIRS can only detect C 2H 2 above the 200 mbar level - although the massive northern hemisphere thunderstorm of 2010/2011 seems able to decrease stratospheric concentrations of C 2H 2. From this, it can be asserted that lightning from normal thunderstorm activity cannot be the key source for upper tropospheric C 2H 2 on Saturn, since the upper-tropospheric concentrations retrieved agree with the concentrations stemming from the photolysis of CH 4 (23 ppbv) from solar radiation penetrating through the Saturnian atmosphere, with an upper limit for lightning-induced C 2H 2 volume mixing ratio of 10 -9. © 2012 Elsevier Ltd. All rights reserved.